ASSESSMENT OF ANHYDRITE DISSOLUTION AS THE RATE-LIMITING STEP DURING THERMOCHEMICAL SULFATE REDUCTION - Bildstein O.; Worden R.H.; Brosse E. (My University, 2001)
Thermochemical sulfate reduction (TSR) is a process observed in some gas and oil reservoirs above a temperature about 120-145°C. During this process, petroleum compounds such as methane react with anhydrite to form calcite, H2S and other minor components. This reaction can lead to the complete destruction of petroleum accompanied by the generation of a large amount of H2S. TSR consists of a variety of more elementary steps, including dissolution of reactants, diffusion to the point of reaction, geochemical interaction in the aqueous phase and mineral precipitation. The rate-controlling step for TSR is as yet unknown, although thermodynamic data suggest that the assemblage of hydrocarbons and anhydrite is very reactive. Experimental work revealed relatively high dissolution rates for anhydrite. Modeling TSR as complex multiphase, multistep reaction confirms that if the intrinsic dissolution of anhydrite were the rate-limiting step, the reaction could be complete within a year and would be effective even at low temperatures (e.g., 80°C). Other controls on the transformation must therefore be invoked. At the reservoir scale, a limited reactive volume at the gas-water transition zone may localize and thus limit the rate of TSR. Textural evidence indicates, however, that the controls on the reaction rate at the grain scale are more important. In model simulations, calcite precipitation on the outer edge of anhydrite nodules leads to progressive isolation of the remaining anhydrite from the petroleum phase and a dramatic decrease in the anhydrite dissolution rate. With the reactants forced to diffuse through the calcite armoring, the simulations predict completion of TSR in 200,000-300,000 years. The simulation results match closely the observed trend of reaction extent as a function of depth for temperature higher than 140°C, but overestimates this extent at lower temperature. Thus, the modeling suggests that the rate-controlling step of TSR evolves initially from (1) the rate of aqueous redox interaction between sulfate and petroleum to (2) the rate of diffusion-controlled dissolution of anhydrite. This could explain the high minimum temperature of reaction as well as the coexistence of anhydrite and petroleum even in reservoirs TSR is at an advanced stage.
Keywords: THERMOCHEMICAL SULFATE REDUCTION; NUMERICAL MODELING; SHRINKING-CORE; METHANE; CALCITE PRECIPITATION; HYDROGEN SULFIDE; ANHYDRITE DISSOLUTION